Capital and cost control systems used in the establishment of the Grootegeluk Coal Mine - G. Ferreira; A. G. R. Coreejes (The Southern African Institute of Mining and Metallurgy, 1982)
The paper sets out briefly the methods used for the planning and control of the construction work at Grootegeluk Coal Mine near EIIisras, Transvaal. It includes a discussion of the programming, the updating of programmes, and the progress reporting.